Tourism transportation: island tourists vehicle / Mazlan Ahmad - Ahmad, Mazlan (2006)
In Malaysia tourism sector have contribute a part of national income. This is because Malaysia have many interesting place for tourism, such as Pangkor, Langkawi , Tioman and many more. At Malaysia tourism is one of the sectors have to be take serious from the transportation aspect. At Pangkor Island have it own transportation for tourist to view the island beauty. Many tourists usually rent a van. The van design must be changed so it will over come the problem been facet by the foreign and local tourist. Research showed that van is the most practical transport used at Pangkor because the road condition has many dangerous corners. It also overcomes the uncomfortable and the safety problem furthermore we hope from the research result the design that will be presented is suitable whit the image of Pangkor Island without forgetting the ergonomic and safeties aspect.